2017
DOI: 10.1159/000452846
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Bilirubin (ALBI) Grade as Part of the Evidence-Based Clinical Practice Guideline for HCC of the Japan Society of Hepatology: A Comparison with the Liver Damage and Child-Pugh Classifications

Abstract: Aim/Background: The purpose of this study was to evaluate the validity of 3 classifications for assessing liver function, the liver damage and Child-Pugh classifications and the newly proposed albumin-bilirubin (ALBI) grade, in order to examine the feasibility of evaluating hepatic function using ALBI grade with the hepatocellular carcinoma (HCC) treatment algorithm used in Japan. Methods: We analyzed the medical records of 3,495 Japanese HCC patients admitted from 2000 to 2015, which were comprised of 1,580 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 37 publications
7
140
0
Order By: Relevance
“…Consistent with previous studies, Hiraoka et al [26] showed that the ALBI grade was superior to the Child-Pugh classification. They also found that the ALBI grade can assess hepatic functional reserve with comparable efficacy to the liver damage grade.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with previous studies, Hiraoka et al [26] showed that the ALBI grade was superior to the Child-Pugh classification. They also found that the ALBI grade can assess hepatic functional reserve with comparable efficacy to the liver damage grade.…”
supporting
confidence: 89%
“…Hiraoka et al [26] performed the first study comparing the ALBI grade with the LCSGJ liver damage grade, and the results were reported in this issue of Liver Cancer . Consistent with previous studies, Hiraoka et al [26] showed that the ALBI grade was superior to the Child-Pugh classification.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We read the paper “Albumin-bilirubin (ALBI) grade as part of the evidence-based clinical practice guideline for HCC of the Japan Society of Hepatology: A comparison with the liver damage and Child-Pugh classifications”, published in a recent issue of Liver Cancer [1], with interest. In this multicenter study including 3,495 patients with hepatocellular carcinoma (HCC) undergoing different therapies, the authors show that the ALBI grade can be used as a marker of liver functional reserve in HCC patients from different geographical regions in Japan.…”
mentioning
confidence: 99%